Poverty, wealth, and well-being : experiencing penia in democratic Athens - Taylor, Claire (Oxford University Press, 2017)
In fifth- and fourth-century BCE Athens 'poverty' encompassed not only destitution, but also the need to work for a living. This volume considers what it meant to be poor in this sense, arguing that it should be understood not just as an economic condition, but also in terms of social relations, capabilities, and well-being